Interstitial granulomatous dermatitis: a rare case report of dermatological manifestation of rheumatoid arthritis - Chandrasekaran, Jagadeesh; Alex, Neetu Mariam (International Journal of Research in Medical Sciences, 2020)
Interstitial granulomatous dermatitis (IGD), a rare dermatological disorder was first described by Ackerman et al, in the year 1993. It is characterized by a heterogeneous clinical spectrum and a specific histopathological pattern. It has been described in association with a number of auto-immune disorders, drugs, fungal infections, and malignancies. It may manifest as papules, patches, plaques, nodules, annular lesions, or less frequently, as described classically, as indurated linear subcutaneous cords. This case is being reported as interstitial granulomatous dermatitis is rare dermatological manifestation of rheumatoid arthritis and presentation as large ulcerated skin lesions is further extremely rare. In this case report we describe a 67-year-old gentleman with Seropositive Rheumatoid arthritis. He presented to our hospital with complaints of multiple well defined skin lesions with pus discharge over lower limbs, trunk and upper limbs. Biopsies from left upper limb and abdomen showed focal necrobiosis with surrounding granulomatous inflammation with rare perivascular granulomas. He was subsequently diagnosed to have interstitial granulomatous dermatitis based on histopathological examination. Interstitial granulomatous dermatitis has been described to be associated with a number of autoimmune conditions and drugs. It is very important for clinicians to have knowledge about this rare skin condition as it may be heralding presentation of a serious underlying condition like lymphoproliferative disorders or solid organ malignancies. There is no specific treatment and causative disease has to be diagnosed and targeted.